Effects of signal peptides on secretion of the Bacillus G1 β-cyclodextrin glucanotransferase in Lactococcus lactis NZ9000 - Subramaniam, Menaga (2013)
Cyclodextrin glucanotransferase, CGTase is an enzyme used in food and pharmaceutical industries to catalyze the formation of cyclodextrin (CD) from starch. CDs are of great interest because of their ability to form inclusion complexes with a guest molecule such as drug which would result in the physiochemical modification of this guest molecule. Although Bacillus and Escherichia coli are known workhorses for expression of heterologous proteins, the production of CGTase in these hosts eventually reduces the quality of the products with the presence of impurities such as proteases and endotoxins. Therefore, the production of CGTase using the food-grade lactic acid bacterium is an attractive alternative and safer strategy to produce CGTase for industrial and pharmaceutical uses. This study was aimed to develop genetically modified Lactococcus lactis NZ9000 strains harboring plasmids that secrete the β-CGTase into the exterior environment. CGTase secretion with the presence of signal peptides namely, SPK1 from Paediococcus pentosaceus K1, USP45 from L. lactis MG1363 and NSP from Bacillus sp. G1 were analysed using SignaIP 4.0 software. From the prediction, SPK1 shows the highest protein grand average of hydropathy, GRAVY (the sum of hydropathy values of all amino acids divided by the protein length) of 1.552 followed by USP45 and NSP with 1.174 and 1.089, respectively. Vectors with different signal peptides fused withCGTase gene were constructed and transformed into L. lactis NZ9000. The formation of halo zones by the transformants on starch plate assay after 24 hr incubation indicated the production and secretion of β-CGTase. The expression of this enzyme in the transformants was further confirmed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS PAGE) and zymogram analysis. A band size of ~75 kDa corresponding to β-CGTase was identified in the extracellular environments of the host after medium optimization. Interestingly, the replacement of glucose by starch in the medium was shown to induce β-CGTase production in L. lactis. The secreted β-CGTase was quantified by the CGTase assay. The use of different signal peptides shows difference in the secretion efficiency of β-CGTase. Although β-CGTase production was comparatively low in NZ:SPK1:CGT, the signal peptide SPK1 used for this strain was shown to have higher secretion efficiency of 49 % compared to the other two signal peptides used in this study which is in agreement with the computational analysis. In shake-flask fermentation, a maximum of 4.23 U/ml of CGTase was obtained at 8 hr of cultivation by NZ:SPK1:CGT. Nevertheless, at 7 hr a higher CGTase yield of 6.21 U/g of starch by NZ:USP:CGT was observed which was two times higher than that achieved by NZ:SPK1:CGT (3.45 U/g of starch) and three times higher than NZ:NSP:CGT (2.36 U/g of starch). Higher CGTase productivity was achieved at 0.53 U/ml.h for both strains NZ:USP:CGT and NZ:SPK1:CGT.